Investigação do quadro audiológico periférico e central de crianças com diabetes mellitus do tipo 1 - Rodor, Alessandra Dias (2010)
Introduction: diabetic mellitus type 1 (DM1) is a disease which attacks especially developing children and causes many complications to them. Among all the effective ones, pay our attention the aspects related to the difficulties on concentration and learning disorders reported and noticed. Aim: investigate the audiologic peripheral and central overview of type 1 mellitus diabetic children, from 8 to 10 years old. Material and methodology: it is an exploring, transverse, descriptive and analytic study made from a sample of 28 diabetic type 1 children, which are seen in the outpatients clinic of the Regional Hospital of Taguatinga HRT, area of research of the Diabetic Foot endocrinology, in Taguatinga city DF. It has been done the amnesis process with the parents caretakers and the children in the same hospital. Then, several exams have been done in neurologic otorhinolaryngologic private clinics